THE OPTIMAL CONTROL PROBLEM AN ENSEMLE TRAJECTORIES FOR ONE MODEL OF DYNAMIC SYSTEM UNDER CONDITIONS INCOMPLETE INFORMATION (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
In the paper we considered  one model of dynamic  system in the form linear  differential inclusion with control parameter and under conditions incomplete information about initial state. The control problem for ensemble trajectories of system according to minimax principle is researched. This control problem is study  with  a methods nonsmooth   and multi-value analysis’s. The necessary and sufficient conditions of  optimality are obtained.